The Effect of Extra Funding for Disadvantaged Pupils on Achievement - Dinand Webbink; Hessel Oosterbeek; Mikael Lindahl; Edwin Leuven (Institute for the Study of Labor (IZA), 2004)
This paper evaluates the effects of two subsidies targeted at disadvantaged pupils in the Netherlands. The first scheme gives primary schools with at least 70 percent minority pupils extra funding for personnel. The second scheme gives primary schools with at least 70 percent pupils from different disadvantaged groups extra funding for computers and software. The cutoffs at 70 percent provide a regression discontinuity design which we exploit in a local difference-in-differences framework. For both subsidies we find negative point estimates. For the personnel subsidy these are in most cases not significantly different from zero. For the computer subsidy we find more evidence of negative effects. We discuss several explanations for these counterintuitive results.
Keywords: J24; I28; I21; 330; policy evaluation; disadvantaged students; computers; teachers; regression discontinuity; Schulfinanzierung; Bildungsniveau; Bildungschancen; Niederlande; Benachteiligte